2014
DOI: 10.4005/jjfs.97.51
|View full text |Cite
|
Sign up to set email alerts
|

Radiocesium in Stem, Branch and Leaf of <i>Cryptomeria japonica</i> and <i>Pinus densiflora</i> Trees:

Abstract: Kuroda et al. Akama et al.Ohashi et al. Bq g of radiocesium was detected in the xylem of Cryptomeria stems. At higher parts of the stems, the heartwood contained more radiocesium than the sapwood. As a stem that had been felled just before the accidental deposition also contained radiocesium in its xylem, we deduced that the radiocesium in xylem was not transferred through the root system but likely translocated from foliage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…Radioactive cesium ( 137 Cs) dispersed into the atmosphere by a nuclear weapon test or power plant accident is transferred into trees mainly by two pathways, namely, foliar uptake and root uptake [1,2]. A major part of the foliar uptake of 137 Cs is assumed to occur shortly after a 137 Cs deposition event, when the fraction of dissolved 137 Cs in throughfall and precipitation is high [3], and can be the major source of initial 137 Cs input to trees that have needles or leaves at the time of the deposition event [4]. Subsequently, as the amount of 137 Cs in throughfall decreases exponentially with time [3,5], root uptake becomes the dominant source of 137 Cs input to trees over the long term [1].…”
Section: Introductionmentioning
confidence: 99%
“…Radioactive cesium ( 137 Cs) dispersed into the atmosphere by a nuclear weapon test or power plant accident is transferred into trees mainly by two pathways, namely, foliar uptake and root uptake [1,2]. A major part of the foliar uptake of 137 Cs is assumed to occur shortly after a 137 Cs deposition event, when the fraction of dissolved 137 Cs in throughfall and precipitation is high [3], and can be the major source of initial 137 Cs input to trees that have needles or leaves at the time of the deposition event [4]. Subsequently, as the amount of 137 Cs in throughfall decreases exponentially with time [3,5], root uptake becomes the dominant source of 137 Cs input to trees over the long term [1].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies in the Fukushima contaminated area related to early 137 Cs distribution in the Japanese forest ecosystems21516171819. Most of these studies began immediately after the accident (main data from 2011 to 2012) and showed that for the evergreen species, interception by canopies was very high (60–90%) due to high canopy closure20.…”
mentioning
confidence: 99%
“…9). 10,32) Although the amount of radioactivity that moved into the heartwood differed along the height of the trunk, the contamination inside the tree was not caused by the transportation of 134 Cs and 137 Cs from the roots. The active part of the roots for most trees is at least 20–30 cm below the surface of the soil, and no radiocesium is present at this depth, which suggests that the roots could not absorb 134 Cs and 137 Cs.…”
Section: Forest Contaminationmentioning
confidence: 99%